1966 YEAR IN THE HISTORY OF RUSSIAN DETECTIVE FICTION: VIKTOR SMIRNOV AND PAVEL SHESTAKOV (Philological Studies, 2019)
The article is devoted to the detective stories by Viktor Smirnov (“Night Motorcyclist” and “As a Woodcock to Its Own Springe”) and Pavel Shestakov (“Through the Maze”), which appeared in 1966. These two novels and novella can be considered as the first full-fledged detective stories published in Russia. The paper shows the gradual transition of the Soviet authors from the police novel to the detective story. This gradualism is explained by the hostile attitude of Soviet censorship to the detective genre. It is indicated that the Soviet police novel was close to the production novel and therefore was recognized as satisfying the requirements of socialist realism. The image of the sleuth in Smirnov’s and Shestakov’s detective stories tends, on the one hand, to the typical investigator from the police novel, on the other – to the typical hero of the detective story. In this time Russian writers do not invent new puzzles, but refer to the puzzles already used by foreign detective writers of the late XIX – first third of XX centuries.
Keywords: detective fiction, Viktor Smirnov, Pavel Shestakov